Perbandingan Proses Legislasi Pajak Penghasilan dalam Sistem Civil Law Indonesia dan Common Law Amerika Serikat - Pranandhi Aristo; Mareno Reven Arrafii; Jovan Yardan Naufal Kurniawan; Nayla Wardah Annisa; Muhammad Irfan Herinanda Putra (Fakultas Hukum, UPN Veteran Jawa Timur, 2026)
Income tax is one of the primary sources of revenue for a country and plays a vital role in maintaining economic stability. Income tax is a levy imposed on individuals once they meet the conditions established by law to be classified as taxpayers. The conditions under which a person is deemed eligible to be subjected to income tax are systematically regulated by the government to determine whether an individual has the capacity to bear such a tax. Every country has its own detailed regulations governing income tax, including the applicable tax rates, the requirements that determine whether an individual or entity is subject to taxation, and the penalties imposed on taxpayers who fail to fulfill their tax obligations. Differences between countries in these regulations inevitably arise due to the distinct legal systems they adopt. In the world today, several legal systems exist, but the two most widely used are the civil law and common law systems. The presence of these legal systems gives each country its own unique characteristics in conducting legal processes. Keywords: Income Tax; Tax Payer; Legal System